Racismo e saúde mental da população negra: o quesito raça/cor e os dados epidemiológicos sobre suicídio no Tocantins de 2016 a 2020 - Santos, Lara Sousa (Universidade Federal do Tocantins, 2023)
The myth that Brazilian society is established as a racial democracy has long been proven, in fact this veracity is proven every day through news in which racial issues are reported as a reason for gratuitous violence, murders, precarious access to health, jobs and so on, in view of this, the present article deals with the relationship between epidemiological and statistical data regarding the suicide of young black people and studies on the subject, more specifically the scarcity of studies and analysis, as well as assistance and public policies available for this specific racial group and for the promotion of their mental health. The academic survey on renowned academic authors who discuss the subject relating both themes or not, and especially how the race/color issue can contribute to the study of suicide and its importance aswell as the history of itsimplementation and use, as well asthe standardization and functionality of systems such as the Mortality Information System and the Brazilian Institute of Geography and Statistics and how they cooperate and their importance in studies such as suicide and racial issues. It's about the invisibility of the subject and the lack of debate on the part of the government, even though suicide is recognized as a public health problem.